The future extent of the Anthropocene epoch: A synthesis ... - Summerhayes, CP; Zalasiewicz, J; Head, MJ; Syvitski, J; Barnosky, AD; Cearreta, A; Fiałkiewicz-Kozieł, B; Grinevald, J; Leinfelder, R; McCarthy, FMG; McNeill; Saito, Y; et al. (Elsevier BV, 2024)
We synthesize research from complementary scientific fields to address the likely future extent and duration of the proposed Anthropocene epoch. Intensification of human-forced climate change began from about 1970 onwards with steepening increases in greenhouse gases, ocean acidification, global temperature and sea level, along with ice loss. The resulting distinction between relatively stable Holocene climatic conditions and those of the proposed Anthropocene epoch is substantial, with many aspects irreversible. The still-rising trajectory of greenhouse gas emissions is leading to yet greater and more permanent divergence of the Anthropocene from the Holocene Earth System. We focus here on the effects of the ensuing climate transformation and its impact on the likely duration of this novel state of the Earth System. Given the magnitude and rapid rise of atmospheric carbon dioxide (CO2), its long lifetime in the atmosphere, and the present disequilibrium in Earth’s energy budget (expressed as the Earth’s ...